2012
DOI: 10.1111/j.1468-3083.2012.04652.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of melanoma with regional lymph node metastases: a population‐based study in France

Abstract: Overall, actual practice was in accordance with French recommendations. The main developments from 2004 to 2008 were the disappearance of adjuvant chemotherapies and a more accurate selection of patients for adjuvant interferon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Most studies on melanoma in the elderly have focused on characteristics of patients and tumors; to our knowledge, none has included comprehensive data on the real management of melanoma on a population basis. Previous studies [18][19][20][21] in 2004 and 2008 provided population-based data on different aspects of diagnosis and/or management of melanoma in a large French geographic area. The present study evaluated to what extent characteristics of primary tumors and their management (including excision, surgical margins, sentinel lymph node biopsy [SLNB], adjuvant therapies, and surveillance procedures) differed in older patients compared with younger ones.…”
mentioning
confidence: 99%
“…Most studies on melanoma in the elderly have focused on characteristics of patients and tumors; to our knowledge, none has included comprehensive data on the real management of melanoma on a population basis. Previous studies [18][19][20][21] in 2004 and 2008 provided population-based data on different aspects of diagnosis and/or management of melanoma in a large French geographic area. The present study evaluated to what extent characteristics of primary tumors and their management (including excision, surgical margins, sentinel lymph node biopsy [SLNB], adjuvant therapies, and surveillance procedures) differed in older patients compared with younger ones.…”
mentioning
confidence: 99%
“…Of treated patients, 40% developed depression or other neuropsychiatric symptoms, and up to 10% of all patients required psychiatric evaluation and treatment, or dose modification 7 . Two French population-based studies reported on small groups of hd-ifn patients 8,9 ; the study by Lévy-Sitbon et al reported that 9 of 36 patients receiving hd-ifn stopped early because of toxicity. No further information about toxicity-such as its nature, timing, or management-was available for those cases.…”
Section: Introductionmentioning
confidence: 99%